Meme Politik sebagai Sarana Kampanye Pasangan Santri di Media Sosial @SyakurAmin pada Pilkada 2024 - Yudha Rizky Pratama Putra; Chotijah Fanaqi; Yandi Hermawandi (MUKASI: Jurnal Ilmu Komunikasi, 2026)
The development of social media has changed the patterns of political communication, where memes have become an effective digital campaign strategy for conveying political messages in a concise, engaging, and easily shareable way. This study originates from the phenomenon of political memes used by the candidate pair Syakur Amin and Putri Karlina in the 2024 Garut Regional Election as a tool to shape their image, reach young voters, and build closeness with the public. The aim of this research is to analyze the types of political memes used by the candidates and to reveal their impact on public perception. The study employs a descriptive qualitative approach using Roland Barthes' semiotic theory, which emphasizes the analysis of signs through denotative, connotative, and myth levels. Data collection techniques include observation of social media posts, interviews with relevant informants, documentation, and literature review. The research results indicate that the five memes used, including humor, populist, educational-cultural, geographical, and campaign identity memes, successfully shaped positive perceptions, increased public participation, and strengthened the emotional connection between candidates and voters. Furthermore, political memes also create a space for more relaxed yet substantial political discussions on social media. Nevertheless, the use of memes in political campaigns must consider ethical aspects to avoid misleading or undermining the quality of local democracy. The conclusion of this study emphasizes that political memes are not merely a form of visual entertainment, but also a powerful, strategic, and highly impactful communication tool in the dynamics of campaigns in the digital era.